Short communication: Disorders of labours in the field of poultry - Kadhim Alabbody, Huda Hameed (International Journal of Psychosocial Rehabilitation, 2021)
Introduction: Maintaining occupational health is important in raising production and keeping human safety. The study aimed to assess the health problems of the poultry sector workers on the farm, processing, and marketing. Methods: The study was conducted with a sample of 150 males and 50 females to assess their health status during the last month in Baghdad. A survey was set that included demographic queries as well as about health problems during this month. Results: Large numbers of the workers suffered from some healthy defects due to daily, unorganized continuous work without new machinery, such as muscular and auricular pains, headaches, defects in the eyes, ears, skin, and upper respiratory tract, or general problems such as fever, emitting, and diarrhea due to contact with the biological agents in the scattering of poultry remains. Conclusion: It’s very necessary to use personal protective equipment. The authority must support the workers economically and ethically through awareness of maintaining their physical and health fitness for preserving the environment and its aesthetics. a